Pengaruh Pemberian Debu Vulkanik Sinabung Terhadap Pertumbuhan dan Produksi Tanaman Padi Varietas Dendang pada Tanah Gambut - HR Ayogi Prana SM; Sarifuddin Sarifuddin; Fauzi Fauzi (Jurnal Agroekoteknologi, 2018)
This study aimed to determine the influence of giving Sinabung volcanic ash about dendang rice plant variety growth and production on the peat soil. This study used a non-factorial randomized block design with treatment V0 (without volcanic ash), V1 (250 g/10 kg wet peat), V2 (500 g/10 kg wet peat), V3 (750 g/10 kg wet peat), V4 (1000 g/10 kg wet peat), V5 (1250 g/10 kg wet peat), V6 (1500 g/10 kg wet peat) with three replications. The result showed that the giving of Sinabung volcanic ash obviously able to increase pH, Electrical Conductivity, Cation Exchange Capacity, Exchangeable Cations (Na, K, Ca, Mg), and         P-available on the  peat soil and obvious influential about the plant growth and production. Keywords: peat soil, rice plant, soil chemical characteristics, volcanic ash.